Nonlocal Problem for Fractional Evolution Equations of Mixed Type with the Measure of Noncompactness - Pengyu Chen; Yongxiang Li (Abstract and Applied Analysis)
A general class of semilinear fractional evolution equations of mixed type with nonlocal conditions on infinite dimensional Banach spaces is concerned. Under more general conditions, the existence of mild solutions and positive mild solutions is obtained by utilizing a new estimation technique of the measure of noncompactness and a new fixed point theorem with respect to convex-power condensing operator.